Reklama biznesi sohasidagi huquqiy muammolar: Reklama faoliyatining fuqarolik huquqiy asoslari - Abdumannobova Moxlaroyim Alimardon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the conditions of the modern economy, a large number of interested parties in all countries of the world are increasingly using non-standard forms, types and means of advertising to meet consumer demand. This requires the regulation of state control of legal norms in the field of advertising activities. Through this article, the basis of regulation of advertising activities in Uzbekistan was analyzed and its civil legal basis was studied. Based on the results of the analysis, the existing shortcomings in the legislation were identified and conclusions were drawn